Designing a Multicriteria WebGIS-Based Pre-Diagnosis Tool for Indoor Radon Potential Assessment - Leonel J. R. Nunes; António Curado; Rolando Azevedo; Joaquim P. Silva; Nuno Lopes; Sérgio Ivan Lopes (Applied Sciences, 2022)
Radon (222Rn) is a well-known source of indoor air contamination since in its gaseous form it is a reported source of ionizing radiation that belongs to the group of rare gases. Radon occurs naturally in soils and rocks and results from the radioactive decay of its longer-lived progenitors, i.e., radium, uranium, and thorium. Radon releases itself from the soil and rocks, which mainly occurs in outdoor environments, not causing any kind of impact due to its fast dilution into the atmosphere. However, when this release occurs in confined and poorly ventilated indoor environments, this release can result in the accumulation of high concentrations of radon gas, being recognized by the World Health Organization (WHO) as the second cause of lung cancer, after smoking. Assessing the indoor radon concentration demands specific know-how involving the implementation of several time-consuming tasks that may include the following stages: (1) radon potential assessment; (2) short-term/long-term radon measurement; (3) laboratory data analysis and processing; and (4) technical reporting. Thus, during stage 1, the use of indirect methods to assess the radon occurrence potential, such as taking advantage of existent natural radiation maps (which have been made available by the uranium mineral prospecting campaigns performed since the early 1950s), is crucial to put forward an ICT (Information and Communication Technology) platform that opens up a straightforward approach for assessing indoor radon potential at an early stage, operating as a pre-diagnosis evaluation tool that is of great value for supporting decision making towards the transition to stage 2, which typically has increased costs due to the need for certified professionals to handle certified instruments for short-term/long-term radon measurement. As a pre-diagnosis tool, the methodology proposed in this article allows the assessment of the radon potential of a specific building through a WebGIS-based platform that adopts ICT and Internet technologies to display and analyze spatially related data, employing a multicriteria approach, including (a) gamma radiation maps, (b) built environment characteristics, and (c) occupancy profile, and thus helping to determine when the radon assessment process should proceed to stage 2, or, alternatively, by eliminating the need to perform additional actions.